Developing research questions : a guide for social scientists - White, Patrick, 1971- (Basingstoke [England] : Palgrave MacMillan, 2009)
A guide to generating, formulating and refining research questions, this book takes the reader through the processes involved in developing'researchable' questions. Common problems and mistakes are identified and the links between research questions and research design are discussed.
Where do research ideas come from? -- What makes a research question? -- What makes a question'researchable'? -- Questions, methods and indicators -- Answering research questions : claims, evidence and warrant.
Includes bibliographical references (p. 124-130) and index.
Keywords: Social sciences -- Research -- Methodology; Social sciences -- Research -- Handbooks, manuals, etc